2017
DOI: 10.1039/c7sm00623c
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the dynamics of elastic and non-elastic deformations across an experimental colloidal Martensitic transition

Abstract: We present a framework to segregate the roles of elastic and non-elastic deformations in the examination of real-space experiments of solid-solid Martensitic transitions. The Martensitic transformation of a bodycentred-tetragonal (BCT) to a body-centred-orthorhombic (BCO) crystal structure has been studied in a model system of micron-scale ionic microgel [1] colloids. Non-affine fluctuations, i.e., displacement fluctuations that do not arise from purely elastic (affine) deformations, are detected in particle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The deformation is measured from a set of fixed reference coordinates. In a series of papers [14][15][16][17][18][19] (see also Appendix A for details) some of us have worked out in detail the statistical thermodynamics of χ i , which quantifies the "non-affine" component of the particle displacements, analytically and numerically for a number of two dimensional (2d) crystals at finite temperature. At any T > 0, X behaves as a regular thermodynamic variable with a well-defined mean and variance ∼ N −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deformation is measured from a set of fixed reference coordinates. In a series of papers [14][15][16][17][18][19] (see also Appendix A for details) some of us have worked out in detail the statistical thermodynamics of χ i , which quantifies the "non-affine" component of the particle displacements, analytically and numerically for a number of two dimensional (2d) crystals at finite temperature. At any T > 0, X behaves as a regular thermodynamic variable with a well-defined mean and variance ∼ N −1 .…”
Section: Introductionmentioning
confidence: 99%
“…1. affine rearrangements of particles such as those resulting from the creation of defects [15,19]. The ensemble average X can be tailored using h X consistent with standard fluctuation response relations [15] and h X can also modify the probability of defects.…”
mentioning
confidence: 99%
“…Later, Yethiraj et al (12) reported evidence for an electric-field driven displacive transformation between a bcc and close-packed (cp) configuration in a 3D colloidal system. Several other studies have subsequently discovered similar behavior in various colloidal systems (13)(14)(15)(16)(17).…”
mentioning
confidence: 65%
“…From Eq. (19) it is clear that χ is a sum over the eigenvalues of (PCP). Each eigenvalue represents the contribution of a specific non-affine mode to χ.…”
Section: Non Affine Fluctuations: the Projection Methodsmentioning
confidence: 99%